Acute Brown-Sequard syndrome following brachial plexus avulsion injury. A report of two cases - Zubair, M.; Ravindran, T.; Chan, C.Y.W.; Saw, L.B.; Kwan, M.K. (2011)
Introduction: Brown-Sequard syndrome is an unusual sequelae of pre-ganglionic brachial plexus injury. There have been sporadic case reports indicating that the cause of this condition is due to tethering of the cord, vascular ischaemia or direct avulsion injury of the nerve roots. This is a report of two patients with complete pre-ganglionic brachial plexus avulsion injuries who developed acute partial Brown-Sequard syndrome due to haematoma. Cases: Two patients developed acute partial Brown-Sequard syndrome associated with complete pre-ganglionic brachial plexus avulsion injuries. In the first case the neurology recovered fully after the evacuation of the large subdural hematoma. Whereas, in the second case the neurology only recovered after 4 weeks closed observation in view of the compression was due to small epidural haematoma. Conclusion: Acute Brown-Sequard syndrome occurring in association brachial plexus injury should be investigated with urgent magnetic resonance imaging to exclude any reversible haematoma compression. (Hong Kong j.emerg.med. 2011;18:347-351)